A new evaluation index for reliquefaction resistance of Toyoura sand. Issue 136 (September 2020) - Iwai, Hiromasa; Ni, Xueqian; Ye, Bin; Nishimura, Nozomi; Zhang, Feng
Abstract: In 2011 off the Pacific coast of Tohoku Earthquake, liquefaction and reliquefaction were observed along 600 km of the Northeast Coast of Japan and the infrastructure in this area experienced severe damage. During the earthquake, the fact that reliquefaction in aftershocks may also cause severe damage to infrastructure draws much attention of the researchers specialized in liquefaction. Researches in the literature indicated that if a sand experienced liquefaction, strong stress-induced anisotropy would occur, which could greatly influence the reliquefaction behavior of sand in aftershocks. Nevertheless, the influence of stress-induced anisotropy on mechanical behavior of sand subjected to cyclic loading has not yet been investigated in laboratory tests. For this reason, a systematic test program was conducted with sequential undrained triaxial cyclic loading tests on Toyoura sand, in which, all the samples were firstly subjected to the same undrained cyclic loading until liquefaction, after which the liquefied samples were fixed at different residual strain and consolidated. Then, the consolidated samples were again subjected to the cyclic loading under undrained condition. It is found that the residual strain will greatly influence the reliquefaction behavior of sand, which clearly indicates the importance of the stress-induced anisotropy formed during the first liquefaction. Based on the testing results, a new index for evaluating the reliquefaction resistance was proposed. Highlights: A unique evaluation method was proposed to evaluate reliquefaction resistance. A proposed parameter was able to evaluate the stress-induced anisotropy and the reliquefaction resistance accurately. A unique relation between relative residual strain and reliquefaction resistance was found for Toyoura sand.